New narratives for innovation. (1st October 2018) - Strand, Roger; Saltelli, Andrea; Giampietro, Mario; Rommetveit, Kjetil; Funtowicz, Silvio
Abstract: Sociotechnical imaginaries are visions of desired social and technological futures created and sustained by stakeholders in science, industry and politics. Within the dominating innovation narratives there are a number of implicit and explicit beliefs that are both descriptive and normative. Technological optimism is the prevailing discourse, challenged by alternative imaginaries, among them a narrative of degrowth. In this paper we argue for the importance of producing more democratic and sustainable imaginations of future social and technological trajectories. We indicate how new narratives for innovation may include different perspectives and sources of knowledge, including heterodox economics, bio-economics, science and technology studies, and Post-Normal Science. The replacement of policy narratives, however, is not achieved through science speaking truth to power. If that were the case, policies would have changed a long time ago. The present analysis and discussion illustrates how the challenge of replacement is itself one that calls for a reflexive understanding of the relationship between knowledge, belief and agency in complex research and innovation (R&I) systems.